Fewpal
+1 vote
104 views
in Mathematics by (29.7k points)

In the figure, ∠PQR = ∠PRQ, then prove that ∠PQS = ∠ PRT. 

1 Answer

+1 vote
by (127k points)
selected by
 
Best answer

∠PQS + ∠PQR = 180° …(1) 

(Linear pair axiom) 

∠PRQ + ∠PRT = 180° …(2) 

(Linear pair axiom) 

But, ∠PQR = ∠PRQ (Given) 

∴ From (1) and (2) 

∠PQS = ∠PRT Proved.

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...